Fourth Generation Cephalosporin Resistance Among Salmonella enterica Serovar Enteritidis Isolates in Shanghai, China Conferred by blaCTX–M–55 Harboring Plasmids - Fu, Ying; Xu, Xuebin; Zhang, Lina; Xiong, Zhiying; Ma, Yeben; Wei, Yihuan; Chen, Zhengquan; Bai, Jie; Liao, Ming; Zhang, Jianmin (Frontiers in Microbiology, 2020)
In this study, we investigated the pattern of antimicrobial resistance in Salmonella enterica serotype Enteritidis isolates in Shanghai, China from 2005 to 2014. We found the first isolates with resistance to the fourth-generation cephalosporin cefepime starting in 2010. Furthermore, we analyzed the epidemic characteristics and mechanisms of underlying cefepime resistance in S. Enteritidis isolates found from 2010. In total, 38 of 2,914 (1.30%) isolates were identified as cefepime-resistant S. Enteritidis (CRSE) isolates by Kirby–Bauer disk diffusion. Two isolates were from animal derived food sources; 36 isolates were from fecal samples of human patients with salmonellosis. Antimicrobial susceptibility testing using the agar dilution method revealed that all CRSE isolates showed additional resistances at least to ceftazidime, cefotaxime, and ampicillin. Additionally, pulsed-field gel electrophoresis (PFGE) profiles indicated that 89.47% of CRSE isolates also displayed similar PFGE patterns. Five types of -lactamase genes, blaCTX-M (100.00%, 38/38), blaSHV (65.79%, 25/38), blaTEM (52.63%, 20/38), blaACC (18.42%, 7/38) and blaPSE (5.26%, 2/38) were detected by PCR and sequencing. Among blaCTX-M genes, blaCTX-M-55 was the dominant type (84.21%, 32/38). Conjugation and transformation experiments along with plasmid replicon typing revealed that blaCTX-M-55 was located on plasmids of various replicon types with sizes ranging from 76.8kb to 138.9kb. Plasmid sequence analysis also showed that the blaCTX-M-55 gene was mobilized mainly by the ISEcp1-blaCTX-M-55-ORF477 transposition unit and had its own ISEcp1-based promoter, which accelerated the expression and transmission of blaCTX-M-55. Analysis of whole genome sequences (Illumina) of one selected transformant SH12G706-C showed high similarity of the blaCTX-M-55 carrying plasmid with the IncI1 plasmid backbone p628-CTX-M of Klebsiella pneumoniae detected in 2010 in China. The present study demonstrated that the blaCTX-M-55 gene mobilized by ISEcp1- blaCTX-M-55 -ORF477 was the main feature shared by CRSE isolates and seems to play an important role for transmission of cefepime resistance. The number of CRSE isolates is rising annually, and the strong dissemination ability of ISEcp1-blaCTX-M-55-ORF477-harboring plasmids among different species represents an important threat to the therapeutic effectiveness of cefepime.